Differentiation between Yeast Species, and Strains within a Species, by Cellular Fatty Acid Analysis. 2. Saccharomyces cerevisiae - Augustyn, O.P.H. (South African Journal of Enology and Viticulture, 2017)
Fatty acid extracts of 50 Saccharomyces cerevisiae strains, grown under rigidly standardised conditions, were subjected to capillary gas chromatographic analysis on a polar column. Strains contained saturated, mono-unsaturated and trace amounts of dienoic fatty acids. The mean relative percentages of 10 fatty acids were used to differentiate between the strains studied. Forty-six strains could be differentiated from all others in the group, based on the criterion that when comparing two strains the CFAP's were considered unique if the MRP's of at least one fatty acid differed at the 1 % level. Holman's Index of Relationship proved to be a useful tool for indicating degree of similarity between fatty acid proftles. Efforts to distinguish between the species Sacch. cerevisiae and Sacch. bayanus were not successful. More analyses on authentic strains (determined by DNA homology) are necessary to confirm whether such a separation is possible or not. Oenologically important changes that occurred in a commercial dried yeast during production were reflected in the fatty acid proftles of the dried products. Index of Relationship between the fatty acid profiles of five other dried yeast products, and the mother cultures from which they were produced, was very high indicating no change during the commercial production phase. Changes, or lack of change, were confirmed by fermentation studies.